Young people's disadvantages on the labour market in Italy: reframing the NEET category. Issue 1 (1st January 2018) - Sergi, Vittorio; Cefalo, Ruggero; Kazepov, Yuri
Abstract: The worsening of young people's condition on the labour market has been described as a long-term trend of contemporary advanced capitalist economies. In recent years, the NEET (not in employment, education or training) label has been increasingly used to assess the integration of young people into the labour market. Does the NEET category adequately grasp the complexity of the underlying processes? In this contribution we will try to answer this question considering the Italian case as an extreme example. Focusing on the features of the youth labour market in Italy, we show the heterogeneity that lies behind the NEET concept, as well as its relationships with the labour market, the education system and welfare institutions. We argue that the institutionalization of NEETs as an analytical category may prove to be problematic as it may fail to identify specific vulnerable subgroups clearly, thereby leading to ineffective one-size-fits-all policy responses.